Democratic practice of managers and quality of administrative management in public educational institutions - Morillo-Flores, John (2020)
The study sought to determine the relationship between democratic praxis and quality in the administrative management of managers in public educational institutions. The research was basic, descriptive-correlational, non-experimental, cross-sectional design. Two questionnaires designed on the Likert scale were used. The population was 235 teachers and the simple random sample of 147 teachers. It was concluded that there was a direct relationship between democratic praxis and quality of administrative management; as well as the level of democratic praxis was low and the level of administrative management was of medium quality in the directors of public educational institutions.